Strategies of Religious Teachers to Overcome Students' Difficulties in Learning Islamic History - Putra, Sudarmadi; Heraldo, Duarte; Rizaq, Muhammad; Kurdi, Muqarramah Sulaiman; Nasiruddin, Nasiruddin; Althafullayya, Muhammad Raffin (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
Learning Islamic history at the school level is important, because learning Islamic history, students can take lessons from past events. Learning Islamic history at this time has not gone well, so students feel bored and bored. This is inseparable from the strategy of religion teachers in teaching. This research is intended to examine the strategy of religion teachers to overcome students' difficulties in learning Islamic history. The method used in this research is a quantitative method, with surveys and in-depth interviews. The research concluded that many religion teachers, especially in teaching Islamic history, cannot control the conditions in the classroom so that many of the students feel bored. There have been efforts made by religious teachers. The efforts made are varying learning methods according to students' learning styles in the classroom and providing interesting teaching materials. The limitation in this study is that researchers only conducted research in one place, researchers hope that future researchers can conduct research on religious teacher strategies to overcome student difficulties in learning Islamic history and develop other strategies.